Hearing the text, seeing the text: Mazamisa on orality and textuality - Hombana, Mphumezi (In die skriflig : tydskrif van die Gereformeerde Teologiese Vereniging, 2025)
Mazamisa, a dialectical thinker, argued in his article Reading from this Place (1991), that orality and textuality are complementary hermeneutical modes. This perspective disrupts the conventional binary that quarries oral traditions against written texts. Instead, a dynamic interplay is proposed where each mode amplifies the other’s interpretive potential. This article revisits Mazamisa’s perspective, investigating how oral traditions and written texts mutually enrich interpretation. Stressing the interaction between storytelling and textuality, the study aims to demonstrate the relevance of this reconciliatory hermeneutic for bridging cultural, historical, and textual divides in modern interpretation. Mazamisa’s vision emerges as a crucial tool for navigating the dynamic relationship between oral and textual traditions in the quest for discovering the meaning of the biblical text.ContributionProf. Welile Mazamisa’s concept of Dialectica Reconciliæ significantly contributes to African biblical hermeneutics by advocating for a dynamic interplay between orality and textuality. By challenging the binary opposition between oral traditions and written texts, Mazamisa promotes their complementary nature, where each mode enhances the interpretive potential of the other. These reconciliatory hermeneutic bridges the cultural and historical divides in South Africa between black and white readings, offering a more inclusive and contextual approach to biblical interpretation in African theological contexts.